Ali Mukhni : Dari Guru Olahraga Hingga Menjadi Bupati Padang Pariaman (1982-2020) - Dwi Atika Surya; Abdul Salam (Jurnal Kronologi, 2023)
This study aims to provide an overview of the life journey and progress of Ali Mukhni from a teacher and his role in leading Padang Pariaman Regency as a Deputy Regent and Regent for 15 years. The author is interested in taking Ali Mukhni's character to write his biography because he has had a career in Padang Pariaman Regency for 15 years and during that time Ali Mukhni has contributed a lot to the progress of Padang Pariaman Regency. For this reason, the first step is to collect data from oral and written sources. The second stage is source criticism, both internal and external sources. Next, the third stage is data analysis and interpretation. Finally, the fourth stage is to describe the results of research in the form of scientific writing in accordance with the rules of historical research. The conclusion of this study is that Ali Mukhni is a character from Pauh Village, Padang Pariaman Regency. Ali Mukhni started his career as a sports teacher in 1982-1987 at SMA 1 Teluk Kuantan, in 1988-1995 STM Negeri Bengkulu, in 1995-2000 SMA Negeri 10 Padang,in 2000-2004 SMAN 1 V Koto Kampung Dalam. Ali Mukhni also served as Deputy Regent in 2005-2010 for five years. Until finally Ali Mukhni served as Regent of Padang Pariaman for two terms until his retirement. Ali Mukhni had many roles for Padang Pariaman Regency.